A study to investigate whether consistent cognitive functioning is characteristic of the child's performance on the Piagetean tests of number, space and time - Wertheimer, E (Department of Psychology, 2015)
The developmental psychology of Jean Piaget has, within recent years, been primarily concerned with an application of his general theory of cognitive development to a wide area of cognitive functioning. Piaget has considered the most obvious facets of man's everyday thinking and reasoning and proposed to show that a rich developmental history underlies even his most common concepts. In so doing, Piaget has broached a topic which is so novel and compelling, and one which lays open such a vast field of research, that one cannot fail to recognize his contribution to psychology in formulating these suggestions alone. Piaget's major theoretical contention is that cognition develops in clear-cut sequential stages alike for every child. Although Piaget has never defined his meaning of "stage", it may be deduced from his prolific writings that he implies by this term a specific developmental "level” in the child during which his cognitive functioning in all areas takes a characteristic form, and can be differentiated, according to clearly defined criteria, from his functioning at another developmental "level". Intelligence, then, is a unitary or global capacity which determines, within small limits, consistent cognitive functioning~ within all areas at any specific time. While Piaget has formulated his theory at great length, and shown on the basis of his research, that specific levels or stages of which he talks emerge broadly at certain ages, he has as yet not introduced an adequate experimental procedure to determine whether a child functions consistently in any one area of cognition, and secondly, whether his level of cognitive·functioning remains significantly stable in a number of different areas, at any one period of development. This would implicitly follow from his theory of a homogeneous intelligence and might perhaps be considered as one of the most fundamental conditions to be substantiated in proof of Piaget's contentions. It is these two specific questions that we propose to answer in the present study. Three Piagetean content areas, those of number, space and time, have been considered·for this purpose.